Numeric Planning with Disjunctive Global Constraints via SMT - Scala, Enrico; Ramírez, Miquel; Haslum, Patrik; Thiebaux, Sylvie (Proceedings of the International Conference on Automated Planning and Scheduling, 2016)
This paper describes a novel encoding for sequential numeric planning into the problem of determining the satisﬁability of a logical theory T. We introduce a novel technique, orthogonal to existing work aiming at producing more succinct encodings that enables the theory solver to roll up an unbounded yet ﬁnite number of instances of an action into a single plan step, greatly reducing the horizon at which T models valid plans. The technique is then extended to deal with problems featuring disjunctive global constraints, in which the state space becomes a non-convex n dimensional polytope. In order to empirically evaluate the encoding, we build a planner, SPRINGROLL, around a state–of–the–art off– the–shelf SMT solver. Experiments on a diverse set of domains are ﬁnally reported, and results show the generality and efﬁciency of the approach.